Republic of South Sudan : Analysis of Juba Distribution Network and Capacity Building Needs in the Electricity Sector - World Bank (Washington, DC, 2014)
This section of the report aims to provide an analysis and propose specific technical plans for investment in the Juba distribution network to carry out emergency upgrades (as a short term measure) and to enable it to absorb possible power that is foreseen to be delivered from possible increase in supply (such as, through the Fula Rapids HPP). The report firstly explains the current Juba grid status, followed by the approach undertaken by the study. Then, it presents the result of gap analysis, concluding with the distribution investment plan and its necessary measures to achieve the target. It is to be noted that in the medium term, a detailed least cost investment plan (LCIP) for the country (planned under ESTAP) will be developed which will provide comprehensive methodology as well as an assessment of appropriate technical standards to be incorporated in development of the South Sudan electrical grid network.